Techno- teaching convergence of blended learning: transitions and prospects - Osbaldo Turpo Gebera (Universidad Politécnica Salesiana, 2013)
Since its emergence in the educational context, the Blended Learning emerges as a modality with its own identity. According to its evolution, runs through presentiality configured contexts and virtuality. In a first stage, stood as a mixed or combined mode, then advanced to integration, which resulted in the dilution of its components. The progressive social changes, technological and cultural towards convergence, today brings a new north-mode, given the confluence of pedagogical and technological mediations in the training process. This position places him in a new trend that more than a possibility, actually represents a more explicable on the future of Blended Learning. The pedagogical and technological convergence of media and resources is a more consistent way to understand the mode, while providing a framework for interpreting the transition and development prospects of the Blended Learning, confluence and continuity and potential scenarios facing the same end: the training.